Myanmaro primus gen. et sp. nov., the first orthoclad (Diptera: Chironomidae) from Cretaceous Burmese amber - Giłka, Wojciech; Makarchenko, Eugenyi A.; Pankowski, Mary K.; Zakrzewska, Marta (Zootaxa, 2019)
A fossil genus Myanmaro gen. nov., with a species M. primus sp. nov. (Diptera, Chironomidae) is described from mid-Cretaceous Burmese amber (~100 Ma). The adult male of the new species shows the wing venation pattern lacking a cross-vein MCu, the fore leg ratio lower than 1, and the gonostylus folded inwards - features typical of the subfamily  Orthocladiinae. A bifid gonostylus, with an articulate, likely movable inner branch, is the character indicating a close relationship between Myanmaro and Diplocladius Kieffer, 1908, the latter genus previously postulated as an early lineage in Orthocladiinae. Several characters, i.e. the structure of tergite IX and the anal point, are defined as generic autapom orphies for Myanmaro. A combination of the shape of hypopygial volsellae (or their absence) and the lack of tibial combs also separate this genus from related extant Orthocladiinae and from the only known Cretaceous extinct orthoclad genus Lebanorthocladius Veltz, Azar et Nel, 2007.